The Effect of Temperature and pH on FeCoNi Film Electrodeposition - Ananda Ico Novtiar Turmiasaputri; Erfan Handoko; Setia Budi (Chemistry and Materials, 2022)
This paper reports the effect of temperature and electrolyte pH on the electrodeposition of FeCoNi film. The FeCoNi electrodeposition was carried out from sulfate solution using the potentiostatic technique. The higher temperature increased deposition rate, thickness of the deposit, and size of the FeCoNi crystallites. The obtained FeCoNi films were characterized by X-ray diffractometer (XRD) and energy dispersive X-Ray (EDX). XRD analysis confirmed typical diffraction patterns of awaruite phase. EDX evaluation indicated that the relative weight increases in pH from 2.5 to 4, the composition of wt% Fe deposited increased from 39.2% to 47.9%, while wt% Co and wt% Ni decreased from 36.2% to 33.5 % and 24.6% to 18.6%.